Robotics and Mechatronics Proceedings of the Fifth IFToMM International Symposium on Robotics & Mechatronics (ISRM 2017) - (Chunhui) Yang, Richard; Takeda, Yukio; Zhang, Chunwei; Fang, Gu.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book gathers the proceedings of the ISRM 2017, the fifth IFToMM International Symposium on Robotics and Mechatronics, which was jointly organised by the School of Computing, Engineering and Mathematics at Western Sydney University, Australia and by the IFToMM Technical Committee on Robotics and Mechatronics. The respective contributions showcase the latest advances, trends and future challenges in Computer Modelling and Simulation, Kinematics and Dynamics of Multi-Body Systems, Advanced Dynamics and Control Methods, Linkages and Mechanical Controls, Parallel Manipulators, Mechanism Design, Sensors and Actuators, Mobile Robotics: Navigation and Motion Planning, Bio-inspired Robotics, Micro/Nano-Robotics and Complex Robotic Systems. .
Architecture choice of a robotic hand for deep-sea exploration based on the expert gestures movements analysis -- A Vision-Based Strategy for a Cost-Effective Flexible Robotic Assembly System without Using RCC Devices and Compliant Control -- A Comparative Survey of Climbing Robots and Arboreal Animals in Scaling Complex Environments -- A Service Baxter Robot in an Office Environment.-The Design of A New Rotary Hexapod with A Single Active Degree of Freedom -- Modelling and model-based control of a four - bar mechanism with a flexible coupler link -- Structural synthesis of 2-DOF, 7-link, 2-basic loops simple and multiple joint mechanisms for robotics -- Numerical synthesis of Stephenson six-bar mechanism using a CAD geometric approach -- Foot Reaction Analysis of Whole Body Dynamic via Screw Theory -- Comparison of motion/force transmissibility in a 3-SPR parallel manipulator and a 6-SPS equivalent mechanism -- Kinematic and Dynamic Dimensional Synthesis of Extended Delta Parallel Robots -- AnInfluence Based Error Identification for Kinematics Calibration of Serial Robotic Manipulators -- Autonomous welding seam detecting and tracking using vision and sound sensors in robotic gas metal arc welding -- Applications of a 3-Revolute Orientation Sensing Mechanism (3-ROSM) in Controlling a Camera -- Contrast Enhancement Using Region Based Image Fusion in Wavelet Domain -- Real-time monitoring of fatigue cracks in machine parts using microwave and laser imaging techniques -- Modeling and Characterization of the Double Helical Compliant Joint.-Optimization of the Geometry of a Cable-Driven Storage and Retrieval System -- Doppler Sonography: A Tele-Operated Assistant to Prevent Musculoskeletal Disorder -- Power Analysis of Epicyclic Gear Transmission for Wind Farm -- Influence of Angular Position of Unbalanced Force on Crack Breathing Mechanism -- The Effect of Elliptical Crack Shape Ratio on the Transverse Trajectory of a Cracked Shaft -- Seismic performance comparison of base-isolated and conventional RC frames compliant with ASCE 7-10 using FAHP method -- A Pitman Style Fiber Bragg Grating Displacement Sensor based on Wedge Cavity Structure.
Keywords: Multibody systems; Vibration; Mechanics, Applied; Control engineering; Robotics; Automation; Machinery; Multibody Systems and Mechanical Vibrations; Control, Robotics, Automation; Machinery and Machine Elements